Achieving a good death for all. (16th September 2010) - Ellershaw, John; Dewar, Steve; Murphy, Deborah
Abstract : A good death for all is now recognised as a priority at societal and political levels. To achieve this goal we need a fundamental shift of emphasis: to train and educate healthcare professionals, to ensure rigorous assessment of new end of life care services that aim to improve quality and choice, and to explore best use of resources.